2021
DOI: 10.1177/0885066620979642
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Failure of Non-Invasive Ventilation With RAM Cannula in Bronchiolitis

Abstract: Introduction: In infants hospitalized for bronchiolitis on non-invasive ventilation (NIV) via the RAM cannula nasal interface, variables predicting subsequent intubation, or NIV non-response, are understudied. We sought to identify predictors of NIV non-response. Methods: We performed a retrospective cohort study in infants admitted for respiratory failure from bronchiolitis placed on NIV in a quaternary children’s hospital. We excluded children with concurrent sepsis, critical congenital heart disease, or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
4
2
0
Order By: Relevance
“…When evaluating our model's feature importance through Shapley additive explanations, we found that features representing physiologic vitals data and F i O 2 parameters were considered important. These findings are consistent with previous reports demonstrating the importance of persistent vital sign abnormalities and other comorbidities (i.e., concurrent bacterial pneumonia, persistent hypercarbia, and history of prematurity) as likely indicators of NIV non-response ( 10 , 13 , 40 42 ). Despite their poor performance predicting flow rate escalation in independent models, the ROX and ROX-HR features within our prediction model were highly valuable.…”
Section: Discussionsupporting
confidence: 93%
“…When evaluating our model's feature importance through Shapley additive explanations, we found that features representing physiologic vitals data and F i O 2 parameters were considered important. These findings are consistent with previous reports demonstrating the importance of persistent vital sign abnormalities and other comorbidities (i.e., concurrent bacterial pneumonia, persistent hypercarbia, and history of prematurity) as likely indicators of NIV non-response ( 10 , 13 , 40 42 ). Despite their poor performance predicting flow rate escalation in independent models, the ROX and ROX-HR features within our prediction model were highly valuable.…”
Section: Discussionsupporting
confidence: 93%
“…While previous trials have compared HFNC and NIV use, the present study is the first multicenter analysis to evaluate risk factors for NIV failure in bronchiolitis. 40,41 Similar to prior single-center work, 42,43 we found higher severity of illness was associated with higher odds of HFNC and NIV failure. Characterizing which patients are likely to be successfully treated with NIV remains an important goal of PICU precision medicine.…”
Section: Discussionsupporting
confidence: 80%
“…The distinct advantages of the study in comparison to prior studies are: (a) the continuous risk-score evaluation allows for continuous monitoring of patient state; (b) EPP enables early alert for healthcare providers to prescribe an appropriate treatment regimen based on the patient's physiological state at that time; and (c) the proposed risk stratification method would allow for identification of different risk groups after observed EPP, which can help identify a high-risk subgroup that has an extremely high likelihood of intubation. Some of the common risk factors associated with failure of non-invasive ventilation in children reported by prior studies [59][60][61][62][63][64][65] include higher FiO2, SpO2/FiO2 ratio, respiratory rate oxygenation index (ratio of SpO2/FiO2 to respiratory rate), heart rate, respiratory rate, younger age, and blood pH. The global variable importance of Model A also suggests corroborating evidence that SpO2, FiO2, age, respiratory rate, tachypnea, etc.…”
Section: Research Contributions and Conclusionsupporting
confidence: 62%